Situational Leadership as View by Nurses in Government and Private Hospitals - Agus Sudrajat, Diwa; Zulfikar, Fikri; Lindayani, Linlin (Journal Of Nursing Practice, 2020)
Background:Leadership as an indicator of the quality of human resources is a very determining factor in the success of an organization such as a hospital. Leadership style depends also on the maturity of individuals or groups as followers. Purpose:The purpose of this study was to exploresituational leadership of head nurse as viewed by nursesin government and private hospitals.this study uses descriptive research method with cross-sectional approach. The time of the study will begin in May 2019 until June 2019. The instrument used in this study was the leadership style questionnaire model of Harsey and Blanchard.Results:The leadership style of head nurse in the majority government hospitals is delegate (38.5%) and followed by the leadership style of consultation (38.5%), participation (18.5%) and at least instruction (13.8%). The leadership style of head nurses in private hospitals is also almost the same as government hospitals where the majority of implementing nurses rate the room head in the delegate style (48%), which is followed by the leadership style of consultation (23%), participation (20%) and most the least is the leadership style of instruction (9%).Conclusion:The leadership style of head nurse both government and private hospitals iwas dominated by delegation and consultation.